1982
DOI: 10.1016/0031-9384(82)90359-6
|View full text |Cite
|
Sign up to set email alerts
|

Lateral hypothalamic stimulation: Stimulus-bound eating and self-deprivation☆

Abstract: Research was undertaken in an attempt to clarify the relationship between stimulus-bound eating and self-deprivation produced by electrical stimulation of the lateral hypothalamus. It was hypothesized that if these two phenomena are mediated through a common population of feeding-related neurons, a significant correlation should be observed between these two behaviors. No significant relationship was discovered among the rats tested for both stimulus-bound eating and self-deprivation. Although this finding by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…behavior and lesions of the LH reduce food intake (Arase et al 1987;Frank et al 1982;Grossman and Grossman 1982;Morgane 1961), and these effects have been shown to interact with taste-guided behavior (Conover and Shizgal 1994;Murzi et al 1986;Touzani and Sclafani 2001;Touzani and Velley 1990;Vasudev et al 1985). Whereas previous experiments in the rat have shown that LH stimulation activates NST neurons known to receive input from tongue afferent neurons (Bereiter et al 1980;Matsuo et al 1984;Murzi et al 1986), the present investigation physiologically confirms a bilateral influence of the LH on the responses of NST neurons to gustatory stimulation of the tongue.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…behavior and lesions of the LH reduce food intake (Arase et al 1987;Frank et al 1982;Grossman and Grossman 1982;Morgane 1961), and these effects have been shown to interact with taste-guided behavior (Conover and Shizgal 1994;Murzi et al 1986;Touzani and Sclafani 2001;Touzani and Velley 1990;Vasudev et al 1985). Whereas previous experiments in the rat have shown that LH stimulation activates NST neurons known to receive input from tongue afferent neurons (Bereiter et al 1980;Matsuo et al 1984;Murzi et al 1986), the present investigation physiologically confirms a bilateral influence of the LH on the responses of NST neurons to gustatory stimulation of the tongue.…”
Section: Discussionsupporting
confidence: 78%
“…Electrical stimulation of the LH enhances the responses of rat NST neurons evoked by chorda tympani (CT) nerve stimulation (Bereiter et al 1980) or by electrical stimulation of the anterior tongue (Matsuo et al 1984). Stimulation of the LH induces feeding behavior (Frank et al 1982;Shiraishi 1991;Sweet et al 1999) and alters taste preference behavior (Vasudev et al 1985) in rats. Lesions of the LH reduce food intake and alter plasma glucose levels and taste preferences (Arase et al 1987;Bernardis et al 1990;Grossman and Grossman 1982;Touzani and Velley 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of the LH produces increases in food intake and alterations in taste preference behavior (Frank et al, 1982;Vasudev et al, 1985), whereas damage to this area has opposite effects (Grossman et al, 1978;Touzani and Velley, 1990). Half of the taste-responsive cells in the NST (49/99) were modulated by LH stimulation (Cho et al, 2002).…”
Section: Lateral Hypothalamusmentioning
confidence: 96%
“…However, access to palatable food dampens the increasing rate of level pressing for stimuli (Routtenberg and Lindy, 1965; Spies, 1965). These classical experiments suggest that 1) Activation of the LHA initiates food intake; 2) LHA stimulation is reinforcing and ‘rewarding’ (Hoebel and Teitelbaum, 1962; Frank et al, 1982); and 3) Pleasure derived from eating palatable foods is more intense than direct activation of the LHA, potentially due to involvement of additional elements of the reward circuitry (Routtenberg and Lindy, 1965; Spies, 1965; Coons and Cruce, 1968; Wise, 1974). Thus, it is likely that the initiation of food intake and the rewarding aspects of hedonic feeding (as well as direct LHA stimulation) are mediated by distinct pathways that converge in the LHA (Frank et al, 1982).…”
Section: The Lateral Hypothalamus (Lha)— the Linker Between The Hypotmentioning
confidence: 99%